Integrated approach of electrical resistivity and borehole logging to determine heterogeneous composition of waste soil. - Omar, Husaini; Md Yusoff, Zainuddin; Mohd Pauzi, Nur Irfah (2011)
The behaviors of waste soil settlement are very challenging to be predicted since the complexity of the waste compositions would cause differential settlement. In order to accurately determine the compositions of waste soil, the integrated approach of electrical resistivity and borehole logging method are used. Two lines of electrical resistivity survey with 200 meters length each and 5 numbers of borehole drilling were conducted. The results indicate that the borehole profile and 2 electrical resistivity survey image have about 80% similarity. The borehole logging data verified the subsurface profile which consists of sandy silts, debris and decayed wood and gravel showing that the waste soil is heterogeneous. The nearest borehole to line 1 and line 2 are BH 2 and BH 5. BH 2 shows that sand and clay layers are the most dominant types of soil found in the area. The clay and sand layer has potential to settle. The depth of the clay and sand layers is approximately 34.5 meters. The depth of the base of waste soil is approximately 40 meters. It is proved that the electrical resistivity and borehole drilling method are the most suitable to determine the thickness of individual layers, depth to the base of the waste mass covering the area.